2008
DOI: 10.1590/s1519-566x2008000400009
|View full text |Cite
|
Sign up to set email alerts
|

Morphological regional differences of epithelial cells along the midgut in Diatraea saccharalis Fabricius (Lepidoptera: Crambidae) larvae

Abstract: Diferenças Morfológicas Regionais das Células Epiteliais ao Longo do Intestino Médio de Larvas deDiatraea saccharalis Fabricius (Lepidoptera: Crambidae)RESUMO -A broca da cana, Diatraea saccharalis Fabricius, é uma praga da cana-de-açúcar e outras plantações. O objetivo deste trabalho foi caracterizar variações morfológicas nas células epiteliais (colunares, caliciformes e regenerativas) ao longo do intestino médio de larvas de D. saccharalis. Fragmentos do intestino médio (anterior, mediano e posterior) foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
5
25
0
Order By: Relevance
“…Such differences could be mainly related to the release of cytoplasmatic portions and apical micro-vesicles toward the lumen, as well as to the high quantity of some organelles as Golgi complex and rough endoplasmic reticulum. Similar observations were detected by Pinheiro and Gregório (2001) in D. saccharalis who reported columnar cells with different aspects regarding the quantity of mitochondria and basal invaginations along the midgut. Besides, the goblet cells actively participated in physiological changes of the midgut, as these cells were also more developed in RL than in SL A. gemmatalis.…”
Section: Discussionsupporting
confidence: 89%
“…Such differences could be mainly related to the release of cytoplasmatic portions and apical micro-vesicles toward the lumen, as well as to the high quantity of some organelles as Golgi complex and rough endoplasmic reticulum. Similar observations were detected by Pinheiro and Gregório (2001) in D. saccharalis who reported columnar cells with different aspects regarding the quantity of mitochondria and basal invaginations along the midgut. Besides, the goblet cells actively participated in physiological changes of the midgut, as these cells were also more developed in RL than in SL A. gemmatalis.…”
Section: Discussionsupporting
confidence: 89%
“…These cells were identified in the present study showing particular characteristics of a pattem similar to the one reported by Correia et al (2008) for S. frugiperda. This pattem only differed by the absence of endocrine cells, since additional ultrastmctural and/or immunohistochemical analyses are required to detect these (Pinheiro et al, 2008;Sousa et al, 2009). The moderate changes observed in the epithelium of the midgut of 5. frugiperda caterpillars are different from those in other noctuids that are susceptible to CrylAc, such as the cotton leafworm, A. argillace (Sousa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among the three regions, the midgut region has particularly been the most studied, because alterations on it affect the growth and development of insects as a result of changes in the physiological events that depend on meal intake, absorption and transformation (Mordue and Blackwell, 1993; Nisbet, 2000; De Sousa et al, 2009). The epithelium of the midgut in Lepidoptera is composed of columnar cells which are responsible for absorption and enzymes secretion, goblet cells for ionic homeostasis, endocrine cells for endocrine function and the regenerative cells for epithelium renewal (Genta et al, 2006; Pinheiro et al, 2008; De Sousa et al, 2009). …”
Section: Biological Activities Of Meliaceae Plants Against Lepidoptermentioning
confidence: 99%